2008
DOI: 10.1021/jp076336d
|View full text |Cite
|
Sign up to set email alerts
|

Variable Absorptance and Emittance Devices for Thermal Control

Abstract: Variable absorptance (R) and variable emittance ( ) devices were developed and tested by electrochemical and optical methods for thermal control applications. A unique concept was investigated whereby a highly reflective metal was reversibly deposited on UV/vis/near-infrared (Mylar) and long-wavelength infrared (ZnSe) transparent substrates. Copper was ultimately chosen as a reflective metal due to its desirable optical characteristics, relatively low toxicity, and well-explored electrochemical deposition/stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…With the development of inexpensive infrared imaging systems and precision guidance technology, the fate of military facilities and soldiers is to be destroyed once military items are detected in a war [14] . It is reported that under the non-sunshine time, the infrared emissivity of green plants, withered grass or rock, and shrub is about 0.45-0.60, 0.65-0.75, and above 0.90, respectively [5,15] .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of inexpensive infrared imaging systems and precision guidance technology, the fate of military facilities and soldiers is to be destroyed once military items are detected in a war [14] . It is reported that under the non-sunshine time, the infrared emissivity of green plants, withered grass or rock, and shrub is about 0.45-0.60, 0.65-0.75, and above 0.90, respectively [5,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the target applications, the alteration of electroactive monomer structure via pre‐ and post‐functionalization is a necessity to afford the desired properties of polymers such as electronic, optical, conductivity, etc. For instance, near‐infrared (NIR) switchable electrochromic materials are attractive candidates for use in thermal control and emission detectors for spacecraft, camouflage materials in warfare, optical communications, and biomedicals …”
Section: Introductionmentioning
confidence: 99%
“…Louvers have also been used for thermal control but macro versions are generally bulky and not suitable for small satellites [14]. Electrochromic surfaces are a promising technology that can vary their emissivity through a wide range by application of a small voltage [15]. These devices, however, require time to adjust to changing environments and exhibit wide fluctuation in their spectral emissivity [16].…”
Section: Introductionmentioning
confidence: 99%